LANGUAGE MAINTENANCE OF BATAK TOBA LANGUAGE AMONG YOUNG GENERATION IN KECAMATAN NAMORAMBE KABUPATEN DELI SERDANG - LUSYANA SITANGGANG; LIDIMAN SAHAT MARATUA SINAGA; ANGGRAINI THESISIA SARAGIH (LINGUISTICA, 2021)
The research was about Language Maintenance of Batak Toba Language among Young Generation in Kecamatan Namorambe, Kabupaten Deli Serdang. This study was conducted by applying the descriptive qualitative method. The data source was taken from the conversations of male and female young generations who live in Namorambe, Kabupaten Deli Serdang. The technique for analyzing the data is descriptive qualitative research based on Miles, Huberman, and Saldana. The result of this research was factors of the Batak Toba Language maintenance of young generation in Kecamatan Namorambe, Kabupaten Deli Serdang are Ethno Linguistic Vitality, Neighborhood Domain (100%), Seeing Each Other Frequently, Family Domain, Visiting Homeland Regularly or Frequently (80%) and Practice Traditional Ceremony (50%). The Ways of Young Generations in maintaining the BTL are Acquisition the Language (100%), Socially Integrated Population of Active Speakers (90%), and Localities of People Habitually Using the Language (80%). The Reasons Young Generations Maintain the BTL are Identity (90%), Prestige or Pride (100%), and Keeping the Language (90%).